EKSPRESI SIKLOOKSIGENASE-2 DAN INFILTRASI SEL INFLAMASI GINGIVA PADA TIKUS YANG DIINDUKSI PERIODONTITIS SETELAH PEMBERIAN EKSTRAK ETANOLIK KULIT MANGGIS - , RENDRA CHRIESTEDY PRASETYA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Periodontitis is a chronic inflammatory periodontal tissues which caused by periodontopathic bacteria. Clinically, this disease characterized by the redness of gingival margin, loss of gingival attachment and alveolar bone resorption. COX-2 is an enzyme which plays an important role in inflammation. The level of this enzyme increases in periodontitis cases. Mangosteen rind has xantone, an antiinflammatory subtance which inhibits the synthesis of PGE2 through inhibition of COX-2 secretion. This research aimed to study the expression of COX-2 and gingival inflammatory cells infiltration in experimental-induced periodontitis in rats after mangosteen rind etanolic extract administration. Forty-eight male wistar rats were used in this study. The experimental periodontitis model was induced by silk ligature, which was placed subgingivally around the neck of the anterior lower teeth for 7 days. After the ligation was taken out, the rats were divided into 4 treatment groups, namely mangosteen rind extract 30 mg/kg, 60 mg/kg, ibuprofen, and saline. The rats were sacrificed on the 1st, 3rd, 5th and 7th day after the treatment. The anterior lower jaws were then processed for paraffin embedded tissue. Hematoxillin Eosin staining was done to examine the number of inflammatory cells infiltration, while immunohistochemistry using antibody anti-COX-2 were done to recognized the COX-2 expression. The number of inflammatory cells was analyzed by Two Way Anova test and COX-2 expression by Kruskall Wallis test. Anova result showed a significant difference among groups (p<0.05) indicating that mangosteen rind etanolic extract affected the number of inflammatory cells infiltration. Kruskall Wallis showed a significant difference among groups (p<0.05) indicating that mangosteen rind etanolic extract affected the expression of COX-2. In conclusion, mangosteen rind etanolic extract reduced gingival inflammatory cells infiltration and COX-2 expression in experimentalinduced periodontitis in rats